(untitled) (Philological Studies, 2019)
In the area of street poetry the end of the 20th century meant a radical turning point. General popularization of internet caused its affirmation in lyrics of the street poetry. The living language directives make authors and authoresses modernize their vocabulary and actualize presented contents using elements of internet environment. At the same time new forms of sound records, communication, advertising, marketing, (self-)promotion etc. have been introduced by internet. The following article will present internet influence on street poetry in America and Slovenia as well. Some examples of the authors` and authoresses` lyrics will also be presented.